2018
DOI: 10.1038/s41396-018-0091-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential for primary productivity in a globally-distributed bacterial phototroph

Abstract: Aerobic anoxygenic phototrophs (AAnPs) are common in marine environments and are associated with photoheterotrophic activity. To date, AAnPs that possess the potential for carbon fixation have not been identified in the surface ocean. Using the Tara Oceans metagenomic dataset, we have identified draft genomes of nine bacteria that possess the genomic potential for anoxygenic phototrophy, carbon fixation via the Calvin-Benson-Bassham cycle, and the oxidation of sulfite and thiosulfate. Forming a monophyletic cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
166
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(188 citation statements)
references
References 22 publications
2
166
0
Order By: Relevance
“…The predicted proteins sequences for each genome were searched (HMMER 43 v.3.1b2; hmmsearch -E 1E-5) using HMM models 380 representing the 16 predominantly syntenic ribosomal proteins identified in Hug et al 44 (2016) (Supplemental Data 1). All proteins with a match to a ribosomal protein model were aligned using MUSCLE 45 (v.3.8.31; -maxiters 8) and automatically trimmed using trimAL 39 (v.1.2rev59; -automated1). All 16 alignments were concatenated and a phylogenetic tree was constructed using FastTree 40 (v.2.1.10; -gamma -lg).…”
mentioning
confidence: 99%
“…The predicted proteins sequences for each genome were searched (HMMER 43 v.3.1b2; hmmsearch -E 1E-5) using HMM models 380 representing the 16 predominantly syntenic ribosomal proteins identified in Hug et al 44 (2016) (Supplemental Data 1). All proteins with a match to a ribosomal protein model were aligned using MUSCLE 45 (v.3.8.31; -maxiters 8) and automatically trimmed using trimAL 39 (v.1.2rev59; -automated1). All 16 alignments were concatenated and a phylogenetic tree was constructed using FastTree 40 (v.2.1.10; -gamma -lg).…”
mentioning
confidence: 99%
“…The phylogenetic tree based on 16 concatenated ribosomal proteins used in (Hug et al , 2016) (Figure 1) was constructed using the methodology outlined in (Graham et al , 2018). Briefly, open reading frames in MAGs and genomes were determined using Prodigal v2.6.3 (Hyatt et al , 2010), and ribosomal proteins were identified from these ORFs with HMMER v3.1b2 using the command hmmsearch with an e-value cutoff of 1E-5 (Eddy, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…High-throughput sequencing of environmental DNA, metagenomic assembly of DNA sequence reads into contigs, and binning of contigs into metagenome-assembled genomes (MAGs) has provided unprecedented insights into the metabolic potential and evolutionary history of many uncultivated lineages (Hug et al , 2016; Brown et al , 2015; Woodcroft et al , 2018; Castelle et al , 2013; Crits-Christoph et al , 2018; Castelle et al , 2015; Anantharaman et al , 2016). In addition to revealing numerous new phyla, MAG analyses have identified new clades of microorganisms within longstanding phylogenetic groups, assigned biogeochemical roles to known but uncultivated lineages, and attributed new functions to diverse relatives of model prokaryotes (Graham et al , 2018; Mondav et al , 2014; Tully, 2019; Boyd et al , 2019; Solden et al , 2016; Singleton et al , 2018; Martinez et al , 2019). With these advances in sequencing technology, a more complex view of microbial evolution and metabolism has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…KEGG annotations can be used to estimate the completeness of various biogeochemically-relevant metabolic pathways in a genome using KEGG-Decoder v.1.0.1 (Graham et al, 2018; https://github.com/bjtully/BioData/tree/master/KEGGDecoder). Users can search genomes based on completeness of a pathway or function of interest.…”
Section: Description Of Methodsmentioning
confidence: 99%